2021
DOI: 10.3390/genes12060907
|View full text |Cite
|
Sign up to set email alerts
|

Co-Regulated Genes and Gene Clusters

Abstract: There are many co-regulated genes in eukaryotic cells. The coordinated activation or repression of such genes occurs at specific stages of differentiation, or under the influence of external stimuli. As a rule, co-regulated genes are dispersed in the genome. However, there are also gene clusters, which contain paralogous genes that encode proteins with similar functions. In this aspect, they differ significantly from bacterial operons containing functionally linked genes that are not paralogs. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 133 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…The locus of genes involved in a functional pathway also has an important influence on the regulation of expression (Razin et al, 2021). Interestingly, we found that the inulin synthesis genes 1‐SST and 1‐FFT were located near each other on the genome for all the four studied species (Figure 5e), and the inulin breakdown genes 1‐FEH I and 1‐FEH II were located near each other for all the studied species except yacon (Figure 5f).…”
Section: Resultsmentioning
confidence: 99%
“…The locus of genes involved in a functional pathway also has an important influence on the regulation of expression (Razin et al, 2021). Interestingly, we found that the inulin synthesis genes 1‐SST and 1‐FFT were located near each other on the genome for all the four studied species (Figure 5e), and the inulin breakdown genes 1‐FEH I and 1‐FEH II were located near each other for all the studied species except yacon (Figure 5f).…”
Section: Resultsmentioning
confidence: 99%
“…However, this mechanism cannot explain the selective activation of certain promoters in clusters of paralogous genes since the promoters of all genes in a cluster contain binding sites for the same transcription factors. Here, again, various strategies are implemented to ensure selective gene activation [ 137 ]. In globin gene clusters, promoters of various genes compete for contact with upstream enhancers (Locus Control Region, LCR); promoters located closer to the LCR along the DNA are preferentially activated [ 138 ].…”
Section: Selective Activation Of Certain Promoters By Remote Enhancersmentioning
confidence: 99%
“…Genes encoding keratins, as well as globins, protocadherins, immunoglobulins, olfactory receptors, KRAB-ZNF TFs, and ribonucleases of the A superfamily, are grouped into relatively compact genomic domains. These loci possess certain common properties, such as preferentially unidirectional transcription, activation, and repression of individual genes in different biological conditions and cell types, and the presence of complex regulatory elements [ 7 ]. Clustered localization implies tight control of the regulatory system within a domain: activation and repression on the principle of “all or nothing” is impossible, and thus “simple solutions” such as changes in the spectrum of expressed TFs are not applicable.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Clustered localization is a conserved feature of keratin genes in terrestrial vertebrates [ 6 ] and suggests the presence of mechanisms for the coordinated keratin gene expression within clusters and on different chromosomes. In higher eukaryotes, gathering paralogous genes into a common cluster usually reflects the necessity to choose one or several of these genes to be expressed whereas keeping the other genes silent [ 7 ]. As shown in studies of several multigenic loci, i.e., protocadherin, immunoglobulin, Hox, and globin gene clusters, reconfiguration of spatial regulatory landscape within gene loci is required for the proper regulation of gene activity during differentiation and development [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%